Unveiling Cultural Wisdom: Hermeneutical Exploration of Sidoarjo Villages' Folklore for Contemporary Relevance: Mengungkap Kearifan Budaya: Eksplorasi Hermeneutika Cerita Rakyat Desa-desa di Sidoarjo untuk Relevansi Kontemporer - Joko Susilo; Muhammad Junaedi; Feri Tirtoni; Vidya Mandarani (Academia Open, 2023)
This research delves into the rich oral folklore tradition across different historical periods in Sidoarjo's villages, spanning from the Kahuripan Prabu Airlangga era to Islamic and Dutch colonial periods. The study aims to hermeneutically interpret these narratives to uncover their profound philosophical and meaningful content, specifically focusing on their potential as positive role models for the younger generation. The selected villages include Bendotretek, Semambung, Becirongengor, Singopadu, and Trompoasri, which hold symbols passed down since the Kahuripan era. This exploration seeks to present these enduring symbols in a contemporary context, aligning with current generational trends. The research outcome offers valuable insights into the cultural heritage's adaptability and relevance, fostering cross-generational understanding and appreciation. Highlight: Temporal Span: Investigates Sidoarjo villages' oral folklore, spanning Kahuripan Prabu Airlangga, Islamic, and Dutch colonial eras. Philosophical Exploration: Utilizes hermeneutical approach to unveil profound meanings and positive role models within the narratives. Generational Alignment: Aligns enduring symbols with contemporary trends, fostering cross-generational appreciation and understanding. Keyword: Folklore, Hermeneutics, Cultural Heritage, Generational Values, Contemporary Relevance